PENDAMPINGAN OLIMPIADE KEBUMIAN INTERNASIONAL - Jarwanto (Nusantara Hasana Journal, 2023)
This Community Service Activity has the theme: "Accompanying the activities of the International Earth Olympiad (Sub Material: Provision of Earth Sciences regarding Mineralogy). This activity was carried out in order to provide knowledge about the branch of geology, namely Mineralogy, as well as solving questions from the International Earth Olympiad, especially in the field of mineralogy, which students and teachers can later use in further learning. The implementation method for this activity is outreach to the community, in this case the students of SMAN 1 Prambanan. The results of the activity are that training participants have knowledge and understanding in earth sciences, especially mineralogy, and training participants have knowledge and understanding in preparing students for the International Earth Olympiad which includes understanding and solving questions, especially mineralogy questions.